MEMBANGUN WAWASAN MODERAT DALAM KONTEKS MASYARAKAT MULTIKULTURAL DENGAN NILAI-NILAI ISLAM: MEMBANGUN WAWASAN MODERAT DALAM KONTEKS MASYARAKAT MULTIKULTURAL DENGAN NILAI-NILAI ISLAM - Ana Saputri, Resti; Suryo Putranto, Rindy; Fifit Setyaningrum, Wahyu (AR ROSYAD: Jurnal Keislaman dan Sosial Humaniora, 2023)
This article discusses efforts to build moderate insight in a multicultural society by utilizing Islamic values as a foundation. This case study aims to discuss how Islamic values, such as tolerance, diversity, and interfaith dialogue, can be a source of inspiration to promote deeper understanding and harmony amidst diversity. The method used is library research. The research results show that in facing the challenges of the complexity of society consisting of various ethnicities, religions and cultures, understanding that diversity is an absolute necessity is the first step in paving the way towards moderate insight. Islamic values, such as justice, view all humans as equal creatures before God, regardless of ethnic or religious background. By adopting this perspective, society can build a strong foundation to overcome differences and prevent conflicts that have the potential to be mutually detrimental. Thus, this article will explore how important it is to build a moderate outlook in a multicultural society by embracing Islamic values. From a deep understanding of tolerance, justice and inclusiveness, it is hoped that society can form a strong foundation to achieve harmonious balance amidst increasingly complex diversity.